A case of rudimentary uterine horns with cervical agenesis with intramural fibroid and bilateral endometrioma - Kumari, Ashwini; Sah, Shanti; Mukherjee, Mala; Anu, Dipti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The objective of the study was to report a case of rudimentary horns of cervical agenesis with intramural fibroid and bilateral endometrioma. A 35-year-old nulligravida with a rare Mullerian anomaly of uterus, cervix and vagina with coexisting fibroid and endometrioma. A definite diagnosis and resection of Mullerian structure and endometrioma. This reports a rare case of occurrence of benign tumor of mesenchymal origin from a non-functioning uterine horn along with features of degeneration with cervical agenesis along with presence of bilateral ovarian endometrioma reinforcing the possibility of coelomic metaplasia theory of its origin.